Ageing and autism: A longitudinal follow-up study of mental health and quality of life in autistic adults - Roestorf, Amanda; Howlin, Patricia; Bowler, Dermot M. (Frontiers in Psychology, 2022)
Background: Poor mental health is known to adversely affect functional abilities, social isolation and quality of life (QoL). It is, therefore, crucial to consider the long-term impacts of mental health conditions as autistic adults grow older. Objectives: To explore, in a group of community-based autistic adults, the extent of: (i) autistic traits, co-occurring physical and mental health conditions; (ii) age-related differences in those conditions, and changes over time; and (iii) their impact on everyday living and QoL. Method: 68 autistic adults (aged 19-80 years) participated in the first study (T1); 49 participants from T1 took part in a follow-up at T2 (mean retest interval 2.4 years). Standardised self-report measures of autistic traits, mental health and QoL were completed at both time points. Results: Over two-thirds (71%) of autistic adult participants experienced at least one co-occurring condition, and over a third (37%) met the criteria for three or more co-occurring conditions. Mental and physical health difficulties were related to autistic traits and difficulties in everyday life and were consistent predictors of poor QoL at T1 and T2. Conclusion: Mental health difficulties in autism persisted into older age and did not improve over time. These findings have important implications for mental health provision for autistic adults in older age.